Simulation and Risk Assessment of Waterlogging Disasters in the Main Urban Area of Xi'an Based on GAST-SWMM Model - ZHANG Wenqing; HOU Jingming; WANG Hangang; WANG Chen; LU Pinpin; XU Hui (Renmin Zhujiang, 2023)
In order to effectively control urban waterlogging disasters,urban waterlogging process simulation based on a numerical model and urban waterlogging risk assessment based on multi-source fusion information have gradually become important non-engineering measures.Taking the central urban area of Xi'an City as the study area,this paper simulated the waterlogging process under rainfall conditions of 5 a, 10 a,30 a,50 a,and 100 a based on the GAST-SWMM model.Combined with the relevant hydraulic factors obtained from simulation,a multi-indicator assessment system was constructed by using natural factors and social factors as the framework for waterlogging risk assessment.The results indicate that the high-risk areas of waterlogging in the study area are mainly distributed on the urban central roads.Under various rainfall conditions,the difference in the proportion of low-risk areas between the multi-indicator comprehensive waterlogging risk assessment and a single waterlogging depth indicator ranges from -50% to -60%,while the difference in the proportion of medium-risk areas ranges from 45% to 60%.Therefore,it is of great significance to conduct urban waterlogging disaster risk assessment based on multi-source fusion information.